HUMANISASI PENDIDIKAN ISLAM MELALUI ANTROPOLOGI TRANSENDENTAL HAMZAH FANSÛRÎ - Nasution, Ismail Fahmi Arrauf (EDUKASIA, 2017)
THE HUMANIZATION OF ISLAMIC EDUCATION THROUGH TRANSENDENTAL ANTROPOLOGY OF HAMZAH FANSURI. Every educational plan surely has an accurate basic assumption about humanity. The failure in determining the accuracy of humanity ontology and epistemology will certainly make the failure of the initiated education implementation. Therefore, every educational implementation must have a humanity philosophical concept in accordance with its ontological and epistemological realities. Islamic education today has not have a clear ontological and epistemological foundation yet. As a result, there are many philosophical issues that arise in the implementation of Islamic education especially dehumanity. This paper examined the philosophical foundations and practices of Islamic education through the transcendental anthropology of Hamzah Fansûrî. The constrtuction of Islamic education humanization was done through Ruba'i Hamzah Fansûrî’s Syair (traditional poetry) which has been explained by his student, Syams al-Dîn al-Sumatra'î. This paper reveals that transcendental anthropology of Hamzah Fansûrî is very suitable with the values of humanity in Pancasila (the philosophical basis of the Indonesian state), therefore, it is worth being the ontological and epistemological basis for the theory and practice of the implementation of Islamic Education in Indonesia. The paper suggests that the teachings of Hamzah Fansûrî be embodied in the basis of various segments of the social sciences, especially Islamic education, in order to create a peaceful and inclusive Islam that fits the noble values of Pancasila.